Ekspres Nasional Berhad then, now and future / Nurhayati Othman - Othman, Nurhayati (1994)
Ekspres Nasional Berhad has expanded its services successfully since it was established on the 10th February 1972. Years passed by and it. has developed tremendously with the existence of new buses namely, TRANSNASIONAL. Concentration will be given to route KL - Kangar - KL and KL - JB - KL since they are the most profitable and very potential route among the ENB major routes. As the back bone to the company, the focus is how to improve the service is vital. It is the purpose of this study to identify the problems and challenges which can ruin the quality and image of the company by referring to the TRANSNASIONAL buses. From the result of the findings, the observation as well as interviews, it was found that most of the passengers are satisfied with the service and willing to use the service again in future. This is because the services provided are ml filling the passengers' needs such as comfortable seats and leg spaces. clean toilet and stopover restaurants, good location of counters and other criteria’s which make the TRANSNASIONAL buses in highly demand. Some recommendations will also be highlighted in this thesis so as to help ENB in improving their services especially to the routes under study which are KL - Kangar - KL and KL - JB - KL. Several recommendations are suggested including on how to improve the company image, using electronic ticketing system, improving the operation system, safety programs for drivers, providing effective passenger information and creating an effective promotional strategy.